The Influence of Learning Media and Competence on Teacher’s Professionalism - Masiyah, Masiyah; Lian, Bukman; Putra, Alhadi Yan (Journal of Social Work and Science Education, 2024)
A teacher’s professionalism is based on their unique competencies and skills in teaching science. High professionalism reflects their commitment to improving professional quality through various methods and strategies. Creativity in learning is essential for the teaching and learning process, covering cognitive, psychomotor, and affective aspects. Teachers must use appropriate media in learning to stimulate students’ thoughts, feelings, attention, and interest. In Lubuk Besar District, Central Bangka Regency, there is a lack of media and educational teaching aids, with many teachers lacking degrees and arriving late. Less varied teaching methods and an old learning paradigm result in passive knowledge delivery. This research focuses on Tk/Paud teachers in Lubuk Besar District, Central Bangka Regency, using quantitative research with a descriptive approach. The results show that learning media has a partial and significant effect on teacher professionalism, with a t value of 17.227 and a significance level of 0.000. Teacher competency also has a partial and significant effect on teacher professionalism, with a t value of 3.970 and a significance level of 0.000. In conclusion, learning media and teacher competency have a simultaneous and significant effect on teacher professionalism, with a t value of 17.227 and a significance level of 0.000.